HUMANISME AJARAN AHIMSA DALAM MEMBANGUN TOLERANSI (Perspektif Mahatma Gandhi) - Widya Sena, I Gusti Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Human is a perfect being compared to other beings. Human perfection can be seen from the ability to think in solving the problems it faces. One of them is the problem of subjectivity. The problem of our self view to the others. It can not be denied in almost every life, most human problems that come to the surface as a form of conflict because of the inequality status in religious, social, political and economic. The doctrine of ahimsa taught by Gandhi to the world is the core of the various spiritual social experiences that we can make as the basic philosophy building, nurturing and fostering of tolerance life. By doing spiritual disciplines like prayer, service, devotion, loyal to the truth and de- veloping universal love as a form of spiritual experiences, the life of the universe will be filled with peace and harmony.